Rumen environmental and nutritional strategies to mitigate emissions from livestock - Chiariotti, Antonella (Cuban Journal of Agricultural Science, 2023)
Methane is the single largest greenhouse gas produced by ruminants, 28-times the warming effect of carbon dioxide. Methane is a by-product of the anaerobic fermentation of carbohydrates and amino acids in the rumen to a lesser extent. It is produced by archaea, and it is considered a loss of feed energy that could otherwise be used for productivity. Economic progress and the world’s growing population will increase meat and milk product demands; when ruminant livestock increase, methane production increases, accelerating global warming in the process inevitably. A massive worldwide research effort has investigated various mitigation strategies that can be grouped into three categories: animal and feed management, diet formulation, and rumen manipulation. These approaches affect directly or indirectly the rumen microbiome thereby reducing rumen methanogenesis. The strategy is to improve forage quality or change the forage type or proportion or add supplements such as probiotics, oils, and enzymes that either reduce methanogenesis or shift the metabolic pathways leading to the H2 reduction as a useful substrate. Methanogens community composition rather than its size seems correlated to methane production and the diversity is influenced by H2 availability and interactions within and between H2-producing microbes in the rumen, so research needs to study the different mechanisms of methanogenesis according to dietary and environmental conditions in different ruminants’ species. Keywords: GHG mitigation strategies, methane, methanogenesis, rumen microbiome